Representações sobre a liderança da macroequipa e das microequipas em contextos de empreendedorismo social - Pais, Celso (2015)
In this article, we show how team leadership is represented in nonprofit organizations. Wedraw upon the concepts of macro-team and micro-team in the social entrepreneurial world.We have studied seven socially enterprising organizations through semi-structured individualand collective interviews with managers, technicians with and without supervisory functions,and workers. The data discussed here underwent an inductive analysis based on the proceduresof grounded-theory. Data analysis indicates the importance of accountable workers both inthe macro and micro-team settings. In addition, top managers should be close to the workersin the operational terrain, thus avoiding disruptions in its relations with subordinates. Theintervieweesdiscourse also translate the need for the leader of micro-teams to act as a facilitator.